2014
DOI: 10.2106/jbjs.m.00453
|View full text |Cite
|
Sign up to set email alerts
|

Single Nucleotide Polymorphisms in Osteogenic Genes in Atrophic Delayed Fracture-Healing

Abstract: Impaired fracture union may have genetic contributions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 52 publications
6
30
0
Order By: Relevance
“…Since myofibroblast numbers are increased during the development of a joint contracture and reach a peak level about 2 weeks after trauma in human tissues and animal models, we have chose a period of 2 weeks for our experiment. 6,88 In our study, the number of myofibroblasts in the posterior joint capsule fell by 40% in rats receiving treatment with losartan and by nearly 70% after atorvastatin administration in comparison to the control. Likewise, the area percentage of myofibroblasts was significantly reduced by about 55% (losartan) and 60% (atorvastatin), respectively.…”
Section: Atorvastatin Inferior Capsulementioning
confidence: 44%
“…Since myofibroblast numbers are increased during the development of a joint contracture and reach a peak level about 2 weeks after trauma in human tissues and animal models, we have chose a period of 2 weeks for our experiment. 6,88 In our study, the number of myofibroblasts in the posterior joint capsule fell by 40% in rats receiving treatment with losartan and by nearly 70% after atorvastatin administration in comparison to the control. Likewise, the area percentage of myofibroblasts was significantly reduced by about 55% (losartan) and 60% (atorvastatin), respectively.…”
Section: Atorvastatin Inferior Capsulementioning
confidence: 44%
“…Sathyendra et al observed genetic risk factors for atrophic nonunion in their study, and they reported that identification of a patient as having a genetic risk of delayed or impaired fracture healing at the time of a fracture may justify more aggressive initial treatment of the fracture. 18 Our hypothesis is similar: if a genetic risk factor can be identified for PJI, more aggressive initial treatment, such as use of antibiotic-laden bone cement for primary joint arthroplasty surgery, may be justified.…”
Section: Discussionmentioning
confidence: 89%
“…No statistically significant association was found between the serum and synovial fluid levels of biomarkers and gene polymorphisms in septic and aseptic groups. Although there is currently no study regarding the relationship between PJI and genetic polymorphisms, several studies 18 , 19 have described a relationship between genetic polymorphisms and bone atrophic nonunion in the orthopedic literature. Sathyendra et al observed genetic risk factors for atrophic nonunion in their study, and they reported that identification of a patient as having a genetic risk of delayed or impaired fracture healing at the time of a fracture may justify more aggressive initial treatment of the fracture.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In one of the first genetic studies of nonunion, 62 individuals with atrophic nonunion were contrasted with 47 individuals with normal healing at a set of common variants in bone morphogenetic protein (BMP) pathway genes (BMP‐2, BMP‐7, NOGGIN, and SMAD6) . Another investigation characterized 33 individuals with nonunion and 29 without, at 144 SNPs across 30 genes . A third study examined 101 individuals with uneventful healing and 66 with nonunion, across five genes (AM5C, BMP4, FGF3, FGF10, and FGFR1) .…”
Section: Discussionmentioning
confidence: 99%